Literary Experiences of Encyclopedist of 18th Century: Jean-Francois Marmontel - M. G. Merkulova; S. A. Gerasimova (Научный диалог, 2022)
The article is devoted to identifying the features of the formation of Jean-Francois Marmontel as a writer, journalist and encyclopedist who made a significant contribution to the literary education of the French society. The relevance of the research topic is due to the study of the views of the scientist that influenced the reception of established and new literary genres of the 18th century. The research methodology is based on a narrative approach in the historiographical perspective, as well as a biographical (cultural-anthropocentric) method that reveals the writer's biography as a typical manifestation of the socio-cultural processes of the age of the Enlightenment. The use of these methods determined the novelty of the study, as it contributed to the consideration of the dynamics of the views of the French educator J.-F. Marmontel and the determination of the degree of his literary contribution to the development of new genres of the moralizing novel and the epic novel, as well as the French Encyclopedia (Encyclopédie, ou Dictionnaire raisonné des sciences, des arts et des metiers). It is proved that for J. F. Marmontel the task of the writer was to educate the reader through his introduction to “belle literacy” (belles lettres). The material of the study was the literary works of J. F. Marmontel in French and Russian: poetic works, moralizing stories, novels, including his articles on literature, published in the first edition of the Encyclopedia. An analysis of the content of the French writer's works shows that they are educational and critical in nature, since their author skillfully mastered many literary genres in practice.